2020
DOI: 10.3390/nu12123780
|View full text |Cite
|
Sign up to set email alerts
|

Selenium and Coenzyme Q10 Supplementation Improves Renal Function in Elderly Deficient in Selenium: Observational Results and Results from a Subgroup Analysis of a Prospective Randomised Double-Blind Placebo-Controlled Trial

Abstract: A low selenium intake is found in European countries, and is associated with increased cardiovascular mortality. There is an association between selenium level and the severity of kidney disease. An association between inflammation and selenium intake is also reported. The coenzyme Q10 level is decreased in kidney disease. The aim of this study was to examine a possible association between selenium and renal function in an elderly population low in selenium and coenzyme Q10, and the impact of intervention with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 56 publications
(29 reference statements)
2
18
0
Order By: Relevance
“…Most of the existing studies on the association between selenium status and CKD focus on the clinical treatment or the molecular level [6,[23][24][25] and have controversial results [5,6,24,25]. Selenium is found in different forms in various foods, greatly affecting absorption [26].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the existing studies on the association between selenium status and CKD focus on the clinical treatment or the molecular level [6,[23][24][25] and have controversial results [5,6,24,25]. Selenium is found in different forms in various foods, greatly affecting absorption [26].…”
Section: Introductionmentioning
confidence: 99%
“…A recent placebo-controlled study of an elderly Swedish population showed an association between low selenium (Se) status and age-related reduction in renal function [71]. In this study, dietary supplementation for four years with selenium 200 µg/day (as SelenoPrecise, Pharma Nord, Denmark) and coenzyme Q 10 , significantly improved kidney function as compared with the functional indices in the placebo group.…”
Section: Selenium-a Renal Protector With Chelating Propertiesmentioning
confidence: 62%
“…As FGF-23 is closely interrelated to the renal function [39], it is not surprising that we also observed an association between renal function and the level of FGF-23. Our group has previously reported increased or conserved renal function in elderly individuals low in selenium and Q 10 upon supplementation with selenium and Q 10 [40]. As several reports point to the fact that there is an intimate relationship between the level of FGF-23 and renal function, the decrease of FGF-23 could simply be a result of the renal effects of the supplementation.…”
Section: Discussionmentioning
confidence: 83%